Onychomycosis caused by dematiaceous fungi: A four-year study among agricultural workers of Assam, India - Parismita Borgohain; Purnima Barua; Lakhi Saikia; Jagadish Mahanta; Dipika Shaw; Shivaprakash Rudramurthy (Mazandaran University of Medical Sciences, 2023)
Background and Purpose: Onychomycosis due to dematiaceous fungi is rarely reported and the identification is also quite tricky due to poor sporulation.The recent emergence of dematiaceous fungi as a cause major of onychomycosis is a matter of concern in the field of mycology.  Therefore, this study aimed to understand the dematiaceous fungi as a possible cause of onychomycosis, especially among agricultural workers. In addition, the evaluation of the antifungal susceptibility patterns gave an idea of the accurate drug that will help in the treatment challenge and prevent antifungal resistance. Materials and Methods: The standard procedure was followed for direct microscopic examination and isolating fungi. Furthermore, antifungal susceptibility testing (AFST) was conducted in accordance with the Clinical and Laboratory Standards Institute (CLSI) M-38-A2 protocol.Results: Both KOH and fungal positivity were recovered in 275 workers out of 356 suspected cases, of which 52% were NDMs, 4.3% were yeast, 28.7% were dermatophytes and 14.9% were sterile hyphae. Among NDMs (52%, n=143), 45.5% (n=65) were hyaline hyphomycetes and 54.5% (n=78) were dematiaceous hyphomycetes. Among dematiaceous fungi, Pestalotiopsis spp., Arthrinium spp., etc. were commonly isolated. Additionally, azoles, amphotericin-B and anidulafungin showed excellent antifungal activity against tested isolates. Conclusion: Dematiaceous fungi are now becoming a potential cause of onychomycosis. A more detailed study is needed on the identification of these emerging isolates and the mode of action of antifungal drugs for a better treatment strategy.